Penerapan Metode Eksperimen Pada Materi Elastisitas Sebagai Upaya Peningkatan Prestasi Belajar Fisika Siswa Kelas XI IPA 1 SMA Negeri 3 Bengkalis - - Suryani (STAIN Bengkalis, 2018)
The action research focused on using experiment method to improve students’ achievement on physics. Experimental Learning method is a way of teaching and learning that involves students experiencing and proving themselves into process of the experimental results. The experiment is expected students’ able to understand the concept of physics. The research was done to know the low physics learning achievement shown by the physics learning outcomes. The study consist two cycles, in each cycle consisting of 4 stages, namely Planning, Implementation, Observation and Reflection. This study involved 22 students of eleventh grade of SMAN 3 Bengkalis. There were 11 males and 11 females. Before implementing the experimental method, the percentage of learning completenes was 13,64%, then after the first cycle was carried out using the experimental method, the students’ learning completenes increase into 54,55%. In the second cycle succeeded in achieving the percentage of learning completenes 81,82%. The finding showed that there was improvement on students learning achivement using experimental method. It means that the experimental method can improve students’ achievement on physics of eleventh grade at SMAN 3 Bengkalis.___________________Keywords: Experimental Method, Physics Learning Outcome